Save as ... digital memories - Garde-Hansen, Joanne; Hoskins, Andrew; Reading, Anna (New York : Palgrave Macmillan, 2009)
This groundbreaking and truly interdisciplinary collection of essays examines how digital media technologies require us to rethink established conceptualisations of human memory in terms of its discourses, forms and practices.
Digital memory discourses. The mediatisation of memory / Andrew Hoskins -- Saving lives: digital biography and life writing / Paul Longley Arthur -- Rewind, remix, rewrite: digital and virtual memory in cyberpunk cinema / Sidney Eve Matrix -- Digital memory forms. Memobilia: the mobile phone and the emergence of wearable memories / Anna Reading -- Remembering and recovering Shanghai: seven Jewish families (re)-connect in cyberspace / Andrew Jakubowicz -- Archiving the gaze: relation-images, adaptation, and digital mnemotechnologies / Bruno Lessard -- Digital memory practices. MyMemories?: personal digital archive fever and Facebook / Joanne Garde-Hansen -- The online Brazilian Museu de Pessoa / Margaret Anne Clarke -- Digital storytelling and the performance of memory / Jenny Kidd -- Remixing memroy in digital media / Shaun Wilson.
boek